The Effect of The Use of Communication Technology And The Role of Public Relation Officer on Employee Performance at PT. Technology successful - Agnita Yolanda; Nurismilida; Fahmi Sulaiman (INFOKUM, 2022)
This study aimed to see the influence and magnitude of the relationship between the use of communication technology and public relations on employee performance at PT Berjaya Indonesia. This company is engaged in engineering technology that produces technological tools. So far, the company has experienced a decline in employee performance, which can be seen in the Human Capital Division report. It is suspected that there is an influence on the use of communication technology and the role of the public relations officer on the performance of company employees. 56 research questionnaires were distributed (based on sampling). The findings revealed that the use of communication technology has a significant (p 0.05) impact on employee performance. The role of the public relations officer also affects employee performance, with a significance value of 0.000–0.05. Simultaneously, both also affect the performance of employees of PT. Berjaya Teknologi with a magnitude of 56.5%.